Starting school and leaving welfare: The impact of public education on lone parents' welfare receipt - Mike Brewer; Claire Crawford (Institute for Fiscal Studies (IFS), 2010)
Childcare costs are often viewed as one of the biggest barriers to work, particularly among lone parents on low incomes. Children in England are typically eligible to start school - and thus access a number of hours of free public education - on 1 September after they turn four. This means that children born one day apart may start school up to one year apart. We exploit this discontinuity to investigate the impact of youngest child being eligible for full-time primary education (relative to part-time nursery education) on welfare receipt and employment patterns amongst lone parents receiving welfare. In contrast to previous studies, we are able to estimate the precise timing (relative to the date when full-time education begins) of any impact on labour supply, by using rich administrative data. Amongst those receiving welfare when their youngest child is aged approximately three and a half, we find a small but significant effect on both employment and welfare receipt (of around 2 percentage points, or 10-15 per cent), which peaks eight to nine months after the child becomes eligible (aged approximately 4 years and 9 months). We also find some evidence of a smaller effect of eligibility for part-time nursery education on lone parents' labour supply. This suggests that the expansion of public education programmes to younger disadvantaged children may only encourage a small number of low income lone parents to return to work.
Keywords: I21; J22; 330; labour supply; school entry; regression discontinuity; lone parents; welfare receipt; Alleinerziehende; Sozialhilfe; Kinder; Schule; Arbeitsangebot; Großbritannien